Blended Training Development on Technical Competency Training for Family Planning Instructors (PKB) with Junior Expert Position in National Population and Family Planning Board - Cucu Nurpalah (Teknodika, 2021)
This study aims to analyze the duties of the junior expert family planning instructors (junior expert PKB), analyze the existing technical training curriculum for the junior expert PKB, design the blended training curriculum for technical training for the junior expert PKB, and evaluate the blended training curriculum for technical training for the junior expert PKB. The method used in this research was design and development, developed by Richey and Klein with three stages: analysis, design and development, and evaluation. In general, the competency standards formulated for the junior expert PKB focus on assessment and evaluation of IEC (information, education, and communication), advocacy, recording and reporting to data and information analysis. Meanwhile, the strategy used in training was blended learning by combining face-to-face learning and e-learning. The evaluation was carried out using portfolio assessment. This training curriculum design was assessed by curriculum and e-learning experts in the form of expert reviews with very good results and suitable for use. Moreover, based on the feasibility test conducted on the user, the blended training curriculum developed was very good and suitable for use in technical competency training for the junior expert PKB